Environmental analysis of quasi-static electric field changes of tropical lightning flashes - Sabri M.H.M.; Ahmad M.R.; Esa M.R.M.; Periannan D.; York S.B.; Mohammad S.A.; Abdul-Malek Z.; Lu G.; Zhang H.; Yusop N.; Cooray V.; Al-Kahtani A.A.; et al. (Cevkor Vakfi, 2023)
cloud to ground lightning; comparative study; electric field; electron; environmental assessment; environmental conditions; environmental factor; lightning; storm; thunderstorm; tropical environment; wave dispersion; Malaysia; Strait of Malacca